Effect of COVID-19 on Canadian Medical Student Attitudes toward Ophthalmology Residency Application - Lo, Cody; Rai, Amandeep; Micieli, Jonathan A. (Journal of Academic Ophthalmology, 2021)
Objective This study aims to survey medical students interested in ophthalmology about how changes in electives and Canadian Residency Matching Service (CaRMS) due to the novel coronavirus disease 2019 (COVID-19) pandemic have affected their attitudes toward applying to ophthalmology residency.Design This is a cross-sectional survey.Participants A total of 32 Canadian medical students interested in ophthalmology responded to the survey.Methods A 32-question survey tool used was developed in consultation with medical students, academic ophthalmologists, and residency program directors. The survey was distributed through e-mail by local ophthalmology interest groups at all of Canada's medical schools.Results Respondents felt that changes in ability to travel for electives significantly decreased their likelihood of applying to ophthalmology residency. Additionally, respondents expressed concerns that lack of travel for electives and in-person CaRMS interviews significantly reduced their chances of successfully matching to ophthalmology. Respondents identified one-on-one video calls with program directors and residents as the initiatives that would best counteract the negative impacts from COVID-19. Increased presence of programs on social media were relatively less valued.Conclusion Canadian medical students interested in ophthalmology have concerns about how changes in electives and the CaRMS match due to COVID-19 will impact their ability to be fairly assessed and successfully match to ophthalmology. Lack of travel for electives and interviews has also resulted in students feeling ill equipped to make informed choices about program selection. However, there remains a sustained interest in ophthalmology among applicants.
Keywords: ophthalmology; medical education; residency